2021
DOI: 10.2174/1573399817666210503133747
|View full text |Cite
|
Sign up to set email alerts
|

Why is the Incidence of Type 1 Diabetes Increasing?

Abstract: : Type 1 diabetes is a condition that can lead to serious long-term complications and can have significant psychological and quality of life implications. Its incidence is increasing in all parts of the world, but the reasons for this are incompletely understood. Genetic factors alone cannot explain such a rapid increase in incidence; therefore, environmental factors must be implicated. Lifestyle factors have been classically associated with type 2 diabetes. However, there are data implicating obesity and insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 199 publications
0
21
0
1
Order By: Relevance
“…However, in Finland, a country with a high incidence of type 1 diabetes, the incidence of type 1 diabetes increased during 1953-2006, but since 2006, that trend has been decreasing 15 . Several factors; for example, obesity (accelerator hypothesis), gut microbiome, exposure to several chemicals and early life factors, including maternal diet, mode of delivery, infant feeding, childhood diet and microbial exposure (hygiene hypothesis), might contribute to the increasing incidence of type 1 diabetes in certain populations 16 . The present study found that type 1 diabetes (62.6%) and type 2 diabetes (30.7%) accounted for the majority of cases with young-onset diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Finland, a country with a high incidence of type 1 diabetes, the incidence of type 1 diabetes increased during 1953-2006, but since 2006, that trend has been decreasing 15 . Several factors; for example, obesity (accelerator hypothesis), gut microbiome, exposure to several chemicals and early life factors, including maternal diet, mode of delivery, infant feeding, childhood diet and microbial exposure (hygiene hypothesis), might contribute to the increasing incidence of type 1 diabetes in certain populations 16 . The present study found that type 1 diabetes (62.6%) and type 2 diabetes (30.7%) accounted for the majority of cases with young-onset diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, sulphur-containing amino acids are associated with increased adiposity [30], whilst branched-chain and aromatic amino acids predict insulin resistance in young adults [31]. Both obesity and insulin resistance have been linked to type 1 diabetes [12]. Likewise, there may be differences in the biological effects of various monounsaturated fatty acids [32].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary factors have been proposed as one potential mechanism [9]. Dietary factors have profound effects on the gut microbiome [10,11], which is thought to play an important role in the pathogenesis of type 1 diabetes [12]. Dietary factors in childhood can also induce islet cell autoimmunity [13,14], possibly mediated by microbiome changes [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of T1D is very complex and depends on numerous heterogeneous aspects ( 19 ). Commonly mentioned are genetic, environmental, immune and recently added are microbiome factors ( Table 1 ).…”
Section: Obesity As a Pathogenic Factor Of Developing T1dmentioning
confidence: 99%